When Treatment Meets Natural History: Understanding Early Dermatitis‐Related Adverse Events in Systemic Atopic Dermatitis Trials - Diego Ruiz Dasilva; Alondra Soto‐Gonzalez; Haya Alkiswani; Graham H. Litchman; Harrison Nguyen; Gil Yosipovitch; Firas George Hougeir; Matthew Zirwas; David Cotter; Brad Glick; E. James Song; Christopher G. Bunick; et al. (JEADV Clinical Practice, 2026)
ABSTRACT Biologics and Janus kinase (JAK) inhibitors have transformed the management of atopic dermatitis (AD), yet some patients experience early worsening of disease activity during treatment initiation. In clinical trials, these events are typically recorded as treatment‐emergent adverse events (TEAEs), most commonly coded as “atopic dermatitis”. We conducted a structured narrative review of phase 3 randomized trials evaluating approved systemic therapies for AD used in combination with background topical therapy. Trials of dupilumab, lebrikizumab, tralokinumab, nemolizumab, upadacitinib, and abrocitinib, including AD UP, JADE COMPARE, LIBERTY AD CHRONOS, ECZTRA 3, ARCADIA 1 and 2, and ADhere were included. Study design characteristics, background topical protocols, rescue therapy rules, dermatitis‐related TEAEs reported during the first 16 weeks of treatment were extracted from published data. Dermatitis TEAEs varied widely, ranging from 1% to 29% in treatment arms and 3% to over 41% in placebo groups. Substantial heterogeneity existed in baseline disease severity, topical therapy requirements, rescue allowances, and whether worsening was protocol‐defined or captured through investigator‐reported MedDRA coding. Because TEAEs labeled as atopic dermatitis may reflect natural disease variability, reporting conventions, or protocol factors rather than direct drug effects, cross‐trial comparisons should be interpreted cautiously. Clinicians are reminded to counsel patients that transient worsening may occur and emphasize the importance of adherence to adjunctive topical therapy. Standardized definitions of AD‐related adverse events are needed to improve interpretability across future trials.